Analisis CR, ROA dan DER Terhadap Pertumbuhan Laba Perusahaan Sub Sektor Keramik, Kaca dan Porselen Yang Terdaftar di BEI Periode 2017 – 2021 - Angreni Krisnawati; Edwin Agus Buniarto; Ririn Wahyu Arida (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
This research aims to see the ability of the Current Ratio, Return on Assets and Debt to Equity Ratio on Profit Growth in the Ceramics, Glass and Porcelain Sub-Sector listed on the Indonesian Stock Exchange for the period 2017 - 2021. Using financial reports obtained from the Indonesian Stock Exchange. The research results show that together the variables Current Ratio, Return On Assets and Debt to Equity Ratio have a positive and significant effect on Profit Growth. The coefficient of determination test shows that it is 40%, while the remaining 60% is influenced by other factors outside the research. Partially, the Current Ratio has a positive and significant effect of 0.0309 and the t-statistic is 2.336784. Partially Return On Assets has a positive and significant effect of 0.0051 and a t-statistic of 2.522635. And partially the Debt to Equity Ratio has a positive and significant effect of 0.0117 and a t-statistic of 2.266093.